جۆراوجۆرییە زمانییەکان لە ڕاگەیاندنی کوردیدا - حەمەغەریب, هێرۆ‌ ئەحمەد (Sulaimani Journal for Humanities, 2022)
The research labeled “Language variation in Kurdish media” is a descriptive analysis to represent the language variation in Kurdish media language, also it is Sociolinguistics analysis of role and importance of media (especially Kurdish satellite channels/deducted to News). This research consists of two chapters, namely introduction, body and conclusion. Chapter one begins with language variation, concept and interpretation, also shows the language function in sociolinguistic views. The second chapter which focuses on language variation in Kurdish media and causes of language variation in media. At end of the research display the most important conclusions.